Forestry in Orissa - Rai, L. (Indian Forester, 1955)
16.9% of the total land area of the state is reserved forest, which is hardly adequate to meet the local demands. There is urgent need to increase the area by rehabilitating and then reserving the Protected forests and the erstwhile zamindari forests now under the management of the Board of Revenue and also by increasing the pace of afforestation. The forest types are Northern tropical semi-evergreen, Northern tropical dry deciduous and moist-deciduous forests with some local variations. Sal ( Shorea robusta ), piasal ( Pterocarpus marsupium), and teak are important tree species and other important forest resources are kendu (Diospyros melanoxylon) leaves, sabai (Eulaliopsis binata ) grass, bamboos and Khair ( Acacia catechu ). The state has a fairly rich fauna.